Kolaborasi dalam Program Inovasi Pembangunan dan Pemberdayaan Kewilayahan di Kelurahan Babakan Ciparay - Irsyad Hanif Isakh; Jessica Claudia Rossa; Kaysea Safadristi Narendragharini; Khairunnisa Sultan Putri (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
The implementation of mental revolution in Indonesia is in line with transformation of the governance. One of the government actions to realize mental revolution is collaboration. This research was conducted to study a collaboration in Program Inovasi Pembangunan dan Pemberdayaan Kewilayahan (PIPPK) at Kelurahan Babakan Ciparay that involves RW, LPM, PKK and Karang Taruna. The research method that used in this paper is qualitative approach. This research refers to the collaboration framework from Linden. The result of this research shows that the collaboration of all stakeholders and society in PIPPK at Kelurahan Babakan Ciparay went well. This can be seen from the basic collaboration that was in place, the relationship between stakeholder went well, the high stakes that was formed, the constituency for collaboration that provided by the stakeholder in the form of engagement, and the collaborative leadership that showed by Lurah Kelurahan Babakan Ciparay. The successful collaboration in PIPPK at Kelurahan Babakan Ciparay supported by characteristic of the community that still in togetherness. However, there are a lot of aspect that must be improved in collaboration at Kelurahan Babakan Ciparay, such as increase social media platform as a toolsof communication and increase innovation in PIPPK’s program.